Pengaruh Biaya Pencegahan, Biaya Penilaian, Biaya Kegagalan Internal, Dan Biaya Kegagalan Eksternal Terhadap Profitabilitas - Yudha, Tri Kartika; Andi, Andi; Rahayu, Sri; Barus, Muhammad Joni (Universitas Islam Islam Sumatera Utara, 2023)
This study aims to examine the effect of Prevention Costs, Assessment Costs, Internal Failure Costs and External Failure Costs on Profitability. In this study the population used is the ceramic, porcelain and glass sub-sector companies listed on the Indonesian Stock Exchange from 2017-2021. The sampling technique used purposive sampling. Purposive sampling is a sampling method that is determined through certain criteria by the researcher. Based on predetermined sample criteria, a sample of 6 companies was obtained. This research was conducted with a period of 5 years, so that the total sample of this study was 30 samples. This study uses secondary data using the company's annual financial statements. The data is taken from the Indonesian Stock Exchange. The data analysis technique uses multiple linear regression analysis techniques using SPSS Version 20. The results of the t-test study show that the variable cost of prevention has a significant negative effect on profitability in porcelain ceramic sub-sector manufacturing companies listed on the BEI, the appraisal cost variable has a significant positive effect on profitability on the porcelain ceramic sub-sector manufacturing companies listed on BEI, the variable cost of internal failure has an effect has a significant positive effect on profitability in the porcelain ceramic sub-sector manufacturing companies listed on the Bei, and the external failure cost variable has no significant effect on the profitability of the porcelain ceramic sub-sector manufacturing companies listed on the Bei. The results of the overall variable F test show that prevention costs, appraisal costs, internal failure costs, and external failure costs have a significant effect on profitability in porcelain ceramic sub-sector manufacturing companies listed on the BEI.